Dysregulation of heterochromatin caused by genomic structural variants may be central to autism spectrum disorder - Garvin, Michael R.; Kainer, David (Frontiers in Molecular Neuroscience, 2025)
IntroductionAutism spectrum disorder (ASD) is a highly heritable and heterogeneous neuropsychiatric condition whose cause is still unknown. A common function of proteins encoded by reported risk-genes for ASD is chromatin modification, but how this biological process relates to neurodevelopment and autism is unknown. We recently reported frequent genomic variants displaying Non-Mendelian inheritance (NMI) patterns in family trios in two cohorts of individuals with autism. These loci represent putative structural variants (SV) and the genes that carry them participate in neurodevelopment, glutamate signaling, and chromatin modification, confirming previous reports and providing greater detail for involvement of these processes in ASD. The majority of these loci were found in non-coding regions of the genome and were enriched for expression quantitative trait loci suggesting that gene dysregulation results from these genomic disruptions rather than alteration of proteins.MethodsHere, we intersected these putative ASD-associated SVs from our earlier work with diverse genome-wide gene regulatory and epigenetic multi-omic layers to identify statistically significant enrichments to understand how they may function to produce autism.ResultsWe find that these loci are enriched in dense heterochromatin and in transcription factor binding sites for SATB1, SRSF9, and NUP98-HOXA9. A model based on our results indicates that the core of ASD may reside in the dysregulation of a process analogous to RNA-induced Initiation of Transcriptional gene silencing that is meant to maintain heterochromatin. This produces SVs in the genes within these chromosomal regions, which also happen to be enriched for those involved in brain development and immune response.DiscussionThis study mechanistically links previously reported ASD-risk genes involved in chromatin remodeling with neurodevelopment and may explain the role of de novo mutations in ASD. Our results suggest that a large portion of the heritable component of autism is the result of changes in genes that control critical epigenetic processes.